Diets of eight fish species from the upper slope off the Wairarapa coast, North Island, New Zealand, with notes on the diets of others - M. R. L. Jones (New Zealand Journal of Marine and Freshwater Research, 2009)
The diets of eight demersal fish species from the upper continental slope (c. 24CM‐50 m) were determined from samples taken during late January and early February 2004, off the Wairarapa coast, North Island, New Zealand. Diets were from a combination of benthopelagic and benthic sources, with most species exhibiting ontogenetic shifts in diet, in that larger‐bodied food (fish and/or natant decapod prawns) was more important in the diets of larger fish. Javelinfish ( Lepidorhynchus denticulatus ), silver roughy ( Hoplostethus mediterraneus ), and capro dory ( Capromimus abbreviatus ) had predominantly benthopelagic diets, whereas the diets of sea perch ( Helicolenus percoides ), Bollons’ rattail ( Caelorinchus bollonsi ), two‐banded rattail (C. biclinozonalis ), and silverside ( Argentina elongata ) were predominantly benthic, with the crab Carcinoplax victoriensis an important food item. The diet of Oliver's rattail (C. oliverianus ) was a mix of benthopelagic and benthic organisms. Generally, levels of dietary overlap between the eight species were low. Overall, the diets of these fish probably reflect regional and seasonal levels of food availability. Notes on food observed in the stomachs of a further 18 species, for which there were fewer than 10 stomach samples per species are also provided.